TENSION TYPE HEADACHE (TTH) - Auliya Nur Muthmainnina; Shahdevi Nandar Kurniawan (Journal of Pain, Headache and Vertigo, 2022)
Tension Type Headache (TTH) is the most common type of headache in all age groups worldwide. Because of its high prevalence and possible association with medical and psychiatric comorbidities, TTH has a large socioeconomic impact. TTH is the type of headache that most patients suffer from, ranging from mild to severe pain that reduces their ability to carry out daily activities. TTH can be classified into an episodic tension-type headache (ETTH) and chronic tension-type headache (CTTH). The lifetime prevalence of TTH is high (78%). Approximately 24% to 37% experience TTH several times a month, 10% experience weekly and 2% to 3% of the population have chronic TTH disease. TTH treatment is carried out with pharmacological and non-pharmacological approaches.